Effects of Great Cormorant (Phalacrocorax carbo sinensis) on the littoral zone primary production of colony islands - Yli-Rosti, Juho (fi=Turun yliopisto|en=University of Turku|, 2017)
The Great Cormorant (Phalacrocorax carbo sinensis) is a piscivorous close to top-predator with dense nesting colonies. I studied how this species affects the underwater primary production on their ‘colony islands’, where they can exert influence via trophic cascades. The term “trophic cascade” means that the abundance of one high trophic level affects not only the adjacent level but also the abundance of all lower trophic levels. It has been thought that great cormorants affect the colony islands’ underwater primary production in two different ways: 1) via a top-down effect, which happens by removing fish that potentially increases herbivore abundances and decreases primary production 2) via a bottom-up effect, by accumulating guano on the colony island where nutrients can leach into the surrounding waters. I tested the underwater primary production of colony islands with three experiments that measured 1) the standing biomass of filamentous algae 2) the growth and herbivory of Fucus vesiculosus (a brown macroalga and an important foundation species in the Baltic Sea) and 3) the underwater light intensity (as a proxy for phytoplankton volume). These tests were carried out at the eight colony islands that are located in the Archipelago- and Bothnian Seas. Each colony island had a control island in its near vicinity. The experiments showed that the colony islands’ underwater primary production is higher than that found at its nearest control islands. While the Fucus vesiculosus had higher biomass, light intensity showed a decrease. It seems that primary production is higher only near the colony islands’ shoreline and in shallow (1 metre) water. It is possible that the number of herbivores around the colony islands is also greater than at the control islands. Although this was not detected in the experiments, it may influence the results of the standing biomass experiment. According to these experiments and previous studies, it is likely that cormorants affect the underwater nature of colony islands mainly through a bottom-up effect, arising from the run-off of nutrients from accumulated guano.
Merimetsojen (Phalacrocorax carbo sinensis) vaikutukset koloniasaaren rantavyöhykkeen perustuotantoon